SOLUTION OF THE PROBLEM OF PLACING MEDICAL FACILITIES IN CITY DEVELOPMENT PROJECTS - Danshyna, S. Yu.; Nechausov, A. S. (Radio Electronics, Computer Science, Control, 2020)
Context. The problem of rational allocation of medical facilities of inhabited locality was considered. Methods of evaluating the effectiveness of using the existing medical network and finding ways to improve it when implementing urban development projects were proposed. Objective. The goal of the work is to build and study the procedure for solving the problem of placing medical facilities, considering the existing infrastructure of the city to fulfill the accessibility requirements. Method. A set of factors that affect the placement of a medical facilities and allow a systematic and reasonable decision to be made in choosing a location has been formed. A method for solving the problem of the location of medical facilities, providing an increase in their accessibility level considering the population, its spatial distribution, existing in the settlement of road junction and traffic congestion is proposed. The procedure for solving the problem is presented in the form of an IDEF0 model. The method is based on geoinformation analysis of data, the results of which by spatial clustering are presented in the form of a set of cartographic models, the aggregate of which allows to form a decision about the location. The method allows to assess the accessibility level of existing medical facilities in the inhabited locality, create a list of places for their possible location, find areas of the locality that are not in the access zone. Results. The method of choosing the location of the medical center has been improved, which makes it possible to make decisions based not only on the shortest distance from the center to the patient, but also on the level of its accessibility. For the first time, the structure of information technology for multivariate analysis of a network of city medical centers for decision support systems using GIS technologies is proposed. Conclusions. The medical facilities location problem, which is in increasing the level of accessibility by expanding the area of medical coverage of the territory in which the city population lives by using GIS was practically fulfilled as an IDEF0 model that defines the procedure for solving the problem and choosing the location of the medical center. The practical significance of obtained results has been proven on a practical example – an analysis of the existing hospital system for the provision of emergency medical care in Kharkiv.